Improvement Of Electric Motor Cooler Design Protection System - Bagus Sholihin; Solly Aryza; Adi Sastra P Tarigan (INFOKUM, 2021)
The drive system is described in detail in this research, since it is the primary component in all circumstances and necessitates cooling machines in industry or at home to have a protection / safety system placed on the motor to prevent losses caused by probable disruptions. Cooling machines are becoming more common nowadays, and each cooling system must have an effective protective mechanism to ensure that the cooling machine's electric motor operates efficiently. Its purpose is to underline the important role of the electric motor protection system in order to guarantee that the engine coolant may be utilized safely and cost effectively for an extended length of time. In terms of electric motor management, safety is grouped into three categories: overload protection, short circuit protection, and short circuit protection and overload protection. Thus, to get the desired outcome, the safety of the electric motor functioning as a controller must be adjusted and thoroughly investigated.